A sequência didática como recurso para o ensino da argumentação : uma experiência na 4ª série do ensino fundamental - Comin, Camila (2009)
This dissertation deals with the teaching of argument in the early years of elementary school. From this perspective, examines, through a bibliographic study and implementation of a didatic sequence developed based on theoretical-methodological references, object of analytic reconstruction, if the elementary school children, aged between nine and ten years, are able to produce argumentative sequences in which the game between argument and counterargument occurs, incorporating them to the production of opinion texts. Investigate, yet, which means are necessary for the production of an appropriate teaching proposal to develop this skill. Contribute to studies on the process of teaching-learning of the argumentation, in particular, texts in which occur the dialogical movement and develop methodological proposals that allow the completion of this educational activity with property are the objectives of this study. The bibliographical study presents an analytical reconstruction of Bronckart, Camps, Dolz, Schneuwly, Noverraz and Bakhtin works, authors that allow a defense in a socio-discursive and interactionist perspective of the teaching language and that justify appropriate educational interventions and qualified seen as teaching and learning tools. The field work has consisted of twelve classes of two hours each ones, including submission of the proposal to students, pre-testing, workshops and post-test, developed in an interior public school in Rio Grande do Sul, with a 4th grade class consisting of 27 students. It´s taken based on the methodological procedures adopted by Dolz (1995) and Camps (1995), which ones consist of didactic intervention produced in the context of teaching sequences, or, even, writing projects. The expectations for this study have been, through effective participation in the teaching sequence developed by the researcher, the 4th grade students would be able to produce texts in which anticipated counterarguments that would reinforce their point of view, which have been proved with the assessment of results, which have indicated that children of this stage of elementary education are able to produce opinion texts in which arise the presence of the structural elements of the argument (premises/point of view, arguments, counterarguments and closing). It´s been concluded further that the teacher must possess skills and knowledge about the types and textual types that will work, so he can insert himself effectively into the teaching-learning process of the text and express terms of reflection on the characteristics and writing limitations, presented by his student, and the exercise in a reflexive and critical stance against the text, identifying and learning about their characteristics and possibilities